2014
DOI: 10.1002/chem.201403237
|View full text |Cite
|
Sign up to set email alerts
|

New Concepts for Designing d10‐M(L)n Catalysts: d Regime, s Regime and Intrinsic Bite‐Angle Flexibility

Abstract: Our aim is to understand the electronic and steric factors that determine the activity and selectivity of transition-metal catalysts for cross-coupling reactions. To this end, we have used the activation strain model to quantum-chemically analyze the activity of catalyst complexes d(10) -M(L)n toward methane C-H oxidative addition. We studied the effect of varying the metal center M along the nine d(10) metal centers of Groups 9, 10, and 11 (M=Co(-), Rh(-), Ir(-), Ni, Pd, Pt, Cu(+), Ag(+), Au(+)), and, for com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
56
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 38 publications
(59 citation statements)
references
References 76 publications
(34 reference statements)
3
56
0
Order By: Relevance
“…In one report, insertion transition states were analyzed for model CH activation reactions between methane and zero-valent group 2 (Be, Mg, and Ca) and group 12 (Zn and Cd) metals [61][62][63][64]. One motivation of this study was to provide an understanding based on transition state interactions why the lowest oxidation state of s-block main-group elements compared to Pd(0) have dramatically larger activation barriers for methane CH bond insertion.…”
Section: [(Hbpym)ptcl]mentioning
confidence: 99%
See 2 more Smart Citations
“…In one report, insertion transition states were analyzed for model CH activation reactions between methane and zero-valent group 2 (Be, Mg, and Ca) and group 12 (Zn and Cd) metals [61][62][63][64]. One motivation of this study was to provide an understanding based on transition state interactions why the lowest oxidation state of s-block main-group elements compared to Pd(0) have dramatically larger activation barriers for methane CH bond insertion.…”
Section: [(Hbpym)ptcl]mentioning
confidence: 99%
“…The Bickelhaupt group also examined model CH activation reactions between methane and low-oxidation state group-11 transition-metal cations Cu(I), Ag(I), and Au(I), with a comparison to Pd(0) [61][62][63][64]. This study revealed that at the beginning of the reaction pathway the low-oxidation state group II cations are more effective electrophiles than Pd(0) due to the much lower energy of the 4s, 5s, or 6s LUMOs.…”
Section: [(Hbpym)ptcl]mentioning
confidence: 99%
See 1 more Smart Citation
“…On the one hand, when X is NH the major contribution to the total strain energy is the deformation associated with the copper(I) complex (ΔEstrain ‡ [(phen)Cu I (NHPh)] = +17.6 kcal/mol vs. ΔEstrain ‡ (PhI) = +12.7 kcal/mol). It is well-known, that such a change in the complex angle is required to achieve the maximum orbital overlap between the interacting orbitals of the fragments [84,85]. In this case, the occupied d orbital should interact with the σ*(C-I) vacant orbital.…”
Section: Resultsmentioning
confidence: 99%
“…It is well-known, that such a change in the complex angle is required to achieve the maximum orbital overlap between the interacting orbitals of the fragments [84,85]. In this case, the occupied d orbital should interact with the σ*(C-I) vacant orbital.…”
Section: Resultsmentioning
confidence: 99%